Mapping the conceptual and intellectual structure of soil health research (1996–2021): a terms co-occurrence and co-cited reference network analysis - Sellami, Mohamed Houssemeddine; Mori, Mauro; Terribile, Fabio (Frontiers in Soil Science, 2025)
Soil health has emerged as a critical area of research due to its role in sustainable agriculture, environmental conservation, ecosystem services and policy frameworks like the EU Soil Strategy. Since the 1990s, research has expanded rapidly, yet unevenly, marked by fragmented thematic priorities and methodological approaches. This study employs bibliometric analyses—term co-occurrence and co-cited reference networks—to map the conceptual and intellectual structure of soil health research from 1996 to 2021. By analyzing 984 peer-reviewed articles, we identified three major research clusters: (1) Agricultural Research & Soil Management, emphasizing agronomic practices such as fertilization and crop yield optimization; (2) Soil Health & Agricultural Sustainability, focusing on carbon dynamics, conservation tillage, and policy alignment; and (3) Microbial Ecology & Soil Health, highlighting soil biota, enzyme activity, and long-term biological impacts. Seminal works by Karlen et al., which established foundational frameworks linking soil quality to ecosystem services, and Mbuthia et al., demonstrating microbial resilience under conservation practices, emerged as pivotal drivers of field evolution. Emerging trends favor sustainable practices, amendments, and biological indicators. The analysis reveals critical gaps, including limited integration of pedological modeling to quantify ecosystem services and insufficient long-term studies on conservation agriculture. These findings advocate interdisciplinary collaboration among agronomists, microbiologists, policymakers, and climate scientists to align soil health metrics with global targets (e.g., SDGs, EU Soil Monitoring Law), providing a roadmap to integrate soil health into climate-smart land-use policies.